Cellular changes of microbial consortium GY1 during decabromodiphenyl ether (BDE-209) biodegradation and identification of strains responsible for BDE-209 degradation in GY1. (June 2020) - Yu, Yuanyuan; Yin, Hua; Huang, Wantang; Peng, Hui; Lu, Guining; Dang, Zhi
Abstract: Microbial consortium remediation has been considered to be a promising technique for BDE-209 elimination in water, soil and sediment. Herein, we studied malondialdehyde (MDA), membrane potential (MP), and reactive active species (ROS) of a microbial consortium GY1 exposed to BDE-209. The results indicated that the microbial antioxidant defense system was vulnerable by BDE-209. Both early and late apoptosis of microbial consortium induced by BDE-209 were observed. The sequencing results revealed that Stenotrophomonas, Microbacterium and Sphingobacterium in GY1 played major roles in BDE-209 degradation. Moreover, a novel facultative anaerobic BDE-209 degrading strain named Microbacterium Y2 was identified from GY1, by which approximately 56.1% of 1 mg/L BDE-209 was degraded within 7 days, and intracellular enzymes of which contributed great to the result. Overall, the current study provided new insights to deeply understand the mechanisms of BDE-209 degradation by microbial consortium. Graphical abstract: Image 1 Highlights: Antioxidant system was activated during BDE-209 degradation by GY1. BDE-209 induced ROS production and promoted lipid peroxidation. BDE-209 induced early apoptosis followed by late apoptosis. The genera involved in BDE-209 degradation in GY1 were confirmed. A novel facultative anaerobic BDE-209 degrading strain in GY1 was identified.